Female voices in the 19th century Cuban press: Domitila García de Coronado (Islas, 2023)
Introduction: This article focuses on the role of women in journalism and literature in Cuba, with a particular emphasis on Domitila García de Coronado, who was the first woman to establish a periodical publication on the island.Methods: To explore this topic, a bibliographic and documentary review was conducted, as it pertains to the history of literature. This approach offers insights into the current state of the subject.Results: The findings highlight the significance of women as creators of literary and journalistic content, extending beyond their role as mere readers. The research confirms the connection between García de Coronado's letters, editorial management, and the independence movement in 19th century Cuba. Furthermore, it recognizes her extensive work, which includes books, articles, reviews, poetry, and her contribution to various media outlets.Conclusions: Domitila García de Coronado emerges as a crucial figure in the history of Cuban journalism and literature. Despite receiving limited recognition, she played a pivotal role in advancing the development of press media and fostering an anti-colonialist spirit. Additionally, she shed light on the contributions of other women in society and within the intellectual circles of the time.
Keywords: Cuban press; Cuban literature; history; Domitila García de Coronado; Cuban women; homeland